Inferior Vena Cava Filter Placement during Pregnancy: An Adjuvant Option When Medical Therapy Fails. (27th May 2013) - Valadares, Sara; Serrano, Fátima; Torres, Rita; Borges, Augusta
Abstract : The authors present a case of a 27-year-old multiparous woman, with multiple thrombophilia, whose pregnancy was complicated with deep venous thrombosis requiring placement of a vena cava filter. At 15th week of gestation, following an acute deep venous thrombosis of the right inferior limb, anticoagulant therapy with low-molecular-weight heparin (LMWH) was instituted without improvement in her clinical status. Subsequently, at 18 weeks of pregnancy, LMWH was switched to warfarin. At 30th week of gestation, the maintenance of high thrombotic risk was the premise for placement of an inferior vena cava filter for prophylaxis of pulmonary embolism during childbirth and postpartum. There were no complications and a vaginal delivery was accomplished at 37 weeks of gestation. Venal placement of inferior vena cava filters is an attractive option as prophylaxis for pulmonary embolism during pregnancy.